(untitled) (Conversatoria Linguistica, 2019)
Topics presented in the paper oscillate around the determinants related to the lexical resource of Russian, Ukrainian and Polish language. Related languages, which often overlap with cultural boundaries and therefore with the limits of styles in material culture, with the boundaries of religion, customs, etc. were presented in the paper. Taking into consideration that ethnicity (derived from the Greek word ethnos meaning race) is an essential feature of a particular ethnic community which is a group of strongly interconnected socio-cultural features indicating diversity and specificity of particular sovereign community, linguistic relations should be considered in terms of both culture and language.